Developing "Pancasila Student Profile" instrument for self-assessment - Sabon, Yuliana Olga Siba; Istiyono, Edi; Widihastuti, Widihastuti (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
Character assessment is critical for understanding student progress and determining policies and measures that must be taken to direct and strengthen positive character. This research falls under the category of R & D. The study aimed to create Pancasila character self-assessment questionnaires for students. The approach of generating effective instruments by Mardapi. As a result of the development, 20 items of valid and reliable instruments were obtained. The Aiken formula and exploratory factor analysis (EFA) are used to prove content validity and construct validity, while the alpha Cronbach formula is used to estimate reliability. The coefficient of reliability is 0.71, and the instrument validity index is 0.97. The instrument is accurate and dependable. Exploratory factor analysis (EFA) yielded seven components that describe Pancasila's ideals: (1) work ethic, (2) open-minded, (3) initiative, (4) values and culture, (5) resilience, (6) faith, peace, and cooperation, and (7) caring. These seven characteristics are included in the Pancasila student profile. The instrument was used to assess the character of 153 students, and the results revealed that the students' overall attitude matched Pancasila's specified character of excellent and good. However, numerous actions must be completed to strengthen Pancasila's character so that Pancasila's student profile can be fulfilled.